Whey protein isolate modified by transglutaminase aggregation and emulsion gel properties. Issue 1 (June 2015) - Qi, Weiwei; Chen, Chong; Liu, Mujun; Yu, Guoping; Cai, Xinghang; Guo, Peipei; Yao, Yuxiu; Mei, Sijie
Abstract: Whey protein isolate and commercial soybean salad oil were used to produce the WPI emulsion dispersions. The properties of TG-catalyzed emulsion gelation produced from WPI emulsion dispersions were investigated by the amount of TG, temperature, pH and reaction time. Specifically, the texture properties (hardness and springiness), water-holding capacity and rheological properties (G' and G") were assessed. The result of Orthogonal tests showed WPI emulsion can form better hardness and springiness gel when the ratio of TG and WPI was 20U/g, pH 7.5, treatment temperature and time were 50°C and 3 h, respectively. The microstructure of TG emulsion gels was more compact, gel pore is smaller, distribution more uniform, the oil droplets size smaller compared with untreated emulsion gels. Compared to the control of rheological properties, G' and G" were significantly increased and G' > G", results showed that the gel was solid state, and TG speeded up the process of gelation.